PEMBUATAN BIOETANOL DARI BIJI JEWAWUT (Setaria italica) DENGAN PROSES HIDROLISIS ENZIMATIS DAN FERMENTASI OLEH Saccharomyces cerevisiae - I Wayan Arief Pradana Putra; Rudi Kartika; Aman S. Panggabean (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2017)
Bioethanol production as a biofuels successor fossil fuels from jewawut seed (Setaria italica) through enzymatic hydrolysis process and fermentation use Saccharomyces cerevisiae has been carried out. This research aimed to determine levels of bioethanol production by various concentration of nutrients added and variation time of fermentation. Hydrolysis process by enzymatic through a liquefaction phase with -amylase and saccharification phase with gluco-amylase. Fermentation process by Spirulina sp. as a sources of nutrients. The result of hydrolysis was fermented by Spirulina sp. added with various at 0,5%; 1,05 and 1,5% (w/v), and then with variation time of fermentation at 5, 7 and 9 days. The highest concentration of bioethanol obtained are in addition of Spirulina sp. at 1,0% (w/v) for 7 days. The result of concentration obtained from density method was 88% and from gas chromatography method was 93,096%.